Vierzig Jahre "Überwachen und Strafen" : zur Aktualität der Foucault'schen Machtanalyse - Rölli, Marc; Nigro, Roberto (2017)
By presenting Discipline and Punish, Michel Foucault published a book 40 years ago that has mixed up the common previous terms of power - and therefore those of the political theory and discourse about freedom as well. This book pursues the issue of what the design of the current balances of power that mesmerize "us" (whom exactly?) is. How topical are Foucault's analyses of discipline, which caused a sensation 40 years ago and have had a wide effect, still today? How can the relationship between biological power and disciplinary power that was central to Foucault be determined in present times? What new forms of powers have developed - and by which contextual means can they become accessible?...